THE LEGAL FORM OF THE REACTION ON THE ADMINISTRATIVE OFFENCE (Law and world, 2018)
The article discusses the problem of separation of legal form of response to administrative offense from the legal form of police prevention measures. The Code of Administrative Offenses of Georgia does not define legal forms of response to administrative violations and, therefore, the police uses legal forms of response defined by the Code of Administrative Offenses of Georgia as preventive measures and response measures to Administrative Offences.